LH/hCG-Receptor Expression May Have a Negative Prognostic Value in Low-Risk Endometrial Cancer - Noci, Ivo; Sorbi, Flavia; Mannini, Luca; Projetto, Elisabetta; Pillozzi, Serena; Ghizzoni, Viola; Lottini, Tiziano; Moncini, Daniela; Baroni, Gianna; Mungai, Francesco; Arcangeli, Annarosa; Fambrini, Massimiliano (Frontiers in Oncology, 2016)
Introduction A 51 year-old woman was diagnosed with endometrial cancer (EC) and underwent surgical staging. Pathological evaluation showed a 2 cm × 1 cm G2 endometrioid EC with a 30% myometrial deep invasion (FIGO Stage 1A). The patient was classified as low risk of recurrence, and no adjuvant treatment was offered. Six months after surgery, the patient developed an early vescico-vaginal recurrence, and chemotherapy treatment was started. Few months later, a subsequent involvement of vaginal wall, ileum, and omentum was detected, and the patient underwent second surgery. Background LH/hCG-receptor (LH/hCG-R) expression has been previously reported to be associated with an invasive phenotype in EC cells. Moreover, in a preclinical mouse model of EC behaves as a prometastatic molecular device. Discussion We analyzed the expression level of LH/hCG-R in cancer specimens collected during surgeries. Molecular and immunohistochemical analyses showed a strong expression of both mRNA and protein for LH/hCG-R in all specimens. Conclusion LH/hCG-R expression may be assessed together with other clinicopathological parameters in order to better predict the risk of recurrence in low-risk EC patients. Further clinical trials are warranted in order to validate LH/hCG-R as biomarker in EC.